Reinforcing the Role of the Gakkumdu Center in Electoral Law Enforcement: A Contemporary Analysis from the Perspective of Fiqh Siyasah Dusturiyah - Efa Rodiah Nur; Liky Faizal; Abd. Qohar; Harapandi Dahri Syahrum (MILRev: Metro Islamic Law Review, 2025)
The Integrated Law Enforcement Center (Sentra Gakkumdu) plays a vital role in ensuring the integrity of General and Regional Elections. However, its effectiveness has always been debated. Data from Lampung Province show an extremely low prosecution rate, indicating entrenched issues in its structure, legal framework, and institutional culture. This study aims to analyze the central causes of Gakkumdu’s ineffectiveness in Lampung and to formulate a concrete, integrated institutional-strengthening model from the perspective of Fiqh Siyasah Dusturiyah. This research employs an integrated socio-legal approach, combining normative legal analysis of legislation with qualitative empirical methods and in-depth interviews conducted through purposive sampling. To maintain methodological consistency, the empirical findings were critically analyzed using Lawrence Friedman’s Legal System Theory (Structure, Substance, Culture). The findings reveal that Gakkumdu’s ineffectiveness stems primarily from: 1) conflicting SOPs regarding evidentiary standards (legal substance); 2) inter-agency ego (legal culture); and 3) the ad hoc status of its personnel (legal structure). Consequently, the proposed strengthening model emphasizes harmonizing technical operational regulations, cultivating a collaborative culture, and evaluating performance based on quantitative metrics to boost the case completion rate. From the perspective of Fiqh Siyasah Dusturiyah, this reinforcement aligns with the core principles of al-mashlahah al-‘ammah (public good) and ‘adl (justice) as the philosophical foundation for political legitimacy. This study concludes that an integrated Gakkumdu strengthening model, informed by FSD, is essential to ensure a transparent electoral process and bolster public trust. It offers a conceptual contribution by bridging empirical legal analysis (Friedman) with Islamic ethical jurisprudence (FSD) in the context of Indonesian election law enforcement.